Perception of Women Farmers Group towards the Use of Home Yards Garden in Supporting Food Diversification in Semidang Aji District OKU Regency - Fitri Yani Susanti; Munajat Munajat; Rini Efrianti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Food diversification is one way to overcome food security problems in Indonesia. Food diversification aims to anticipate crises, provide alternative food, stimulate the economy and create healthy human resources. With the target of reducing dependence on rice consumption, Semidang Aji District is one of the districts in Ogan Komering Ulu Regency that participates in the Accelerated Food Consumption Diversification (P2KP) program. Through this P2KP program, the community is directly involved in efforts to improve family welfare, including through diversification of food consumption and home yard utilization. This study aims to find out the perception of women farmers groups on home yard functions in Semidang Aji District, Ogan Komering Ulu Regency, and to find out the perception of women farmers groups towards food diversification in Semidang Aji District, Ogan Komering Ulu Regency. The sampling method used in this study is simple randomness, where from 21 villages in Semidang Aji District, Ogan Komering Ulu Regency, there are 10 villages each with one group of peasant women so there are a total of 10 groups of women. Farmer. Of these 10 groups of female farmers, 10 members were taken as randomly taken respondents, so the total sample of this study was 100 people. The measured level of perception is the perception of female farmers about yard function and women's perception of food diversification. Perception level measurement uses the Likert Scale, which is a research scale commonly used to measure attitudes and opinions. The perception of female farmers in Semidang Aji District, Ogan Komering Ulu Regency towards the function of the home yard garden is in a high category, and food diversification is in a very high category. In addition, it was also found that female farmers in Semidang Aji District, Ogan Komering Ulu Regency, agreed with the statement that the function of the home yard garden can support family food consumption, food diversification can support family food consumption and home yard functions and food diversification together can support family food consumption.